2020
DOI: 10.1097/ccm.0000000000004124
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Performance of Pulmonary Ultrasound, Chest Radiograph, and CT Among Patients With Acute Respiratory Failure*

Abstract: Objectives: The study goal was to concurrently evaluate agreement of a 9-point pulmonary ultrasound protocol and portable chest radiograph with chest CT for localization of pathology to the correct lung and also to specific anatomic lobes among a diverse group of intubated patients with acute respiratory failure. Design: Prospective cohort study. Setting: Medical, surgical, and neurologic ICUs at a 670-bed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 25 publications
1
53
0
4
Order By: Relevance
“…13,14 Other studies have shown that LUS is superior to clinical evaluation and chest radiography for the diagnosis of lung involvement. 15 The findings in this report raise the question of whether the severity of LUS findings can be used to differentiate minor from severe disease in this pandemic, or if home ultrasonography could be a novel care path worth exploring for borderline patients as a means of extending hospital capacity.…”
Section: Day 35 A-linesmentioning
confidence: 93%
“…13,14 Other studies have shown that LUS is superior to clinical evaluation and chest radiography for the diagnosis of lung involvement. 15 The findings in this report raise the question of whether the severity of LUS findings can be used to differentiate minor from severe disease in this pandemic, or if home ultrasonography could be a novel care path worth exploring for borderline patients as a means of extending hospital capacity.…”
Section: Day 35 A-linesmentioning
confidence: 93%
“…One study compared different imaging modalities in intensive care unit revealed high agreement between LUS and CT. The same authors appreciate the role of LUS in exclusion of other pulmonary diseases [e.g., pneumothorax and effusion] [27] .…”
Section: Disucssionmentioning
confidence: 93%
“…The sonographic appearances of interstitial pneumonitis have been well-described in COVID-19 patients, 2,3 and numerous anecdotes and case series 4 demonstrate interstitial or 'ground glass' changes on CT even when patients are asymptomatic. We also know that lung ultrasound approximates CT in diagnostic accuracy when visualising lung parenchyma Authors: A consultant in acute medicine, East Surrey Hospital, Redhill, UK; B consultant in acute and intensive care medicine, Royal Berkshire Hospital, Reading, UK; C consultant in acute and intensive care medicine, William Harvey Hospital, Ashford, UK in patients with respiratory failure, 5 and perhaps is even more sensitive than CT in the diagnosis of COVID-19. 6 Therefore, LUS may be expected to pick up changes related to COVID-19 even in asymptomatic or mildly symptomatic patients, adding diagnostic accuracy to the RT-PCR screening process.…”
Section: Combining Lung Ultrasound With Swab Testing To Improve Test mentioning
confidence: 99%